Cognitive mechanisms predicting resilient functioning in adolescence: Evidence from the CogBIAS longitudinal study. (16th February 2022) - Booth, Charlotte; Songco, Annabel; Parsons, Sam; Fox, Elaine
Abstract: Resilience is a dynamic process depicted by better than expected levels of functioning in response to significant adversity. This can be assessed statistically, by taking the residuals from a model of psychological functioning regressed onto negative life events. We report the first study to investigate multiple cognitive factors in relation to this depiction of resilient functioning. Life events, internalizing symptoms, and a range of cognitive risk and protective factors were assessed in a large sample of adolescents ( N = 504) across three waves spaced 12–18 months apart. Adolescents who displayed fewer symptoms than expected, relative to negative life events, were considered more resilient. Adolescents who displayed more symptoms than expected, relative to negative life events, were considered less resilient. All cognitive factors were associated with resilient functioning to differing degrees. These included memory bias, interpretation bias, worry, rumination, self-esteem, and self-reported trait resilience. Regression models showed that memory bias was a key factor explaining unique variance in prospective resilient functioning. In a subsequent cross-lagged panel model, memory bias and resilient functioning were reinforcing mechanisms across time points, supporting cognitive models of emotional resilience. This study adds to the literature, by highlighting key cognitive mechanisms as potential intervention targets